Analytical solutions for non-uniformity of energy release rate of orthotropic double cantilever beam specimens with an adhesive layer. (September 2016) - Jiang, Zhengwen; Wan, Shui; Li, Minghong; Ma, Lei
Highlights: Effects of deformation and rotational angle at the crack front are incorporated. Closed-form solutions for β and ν are obtained. G Ic can be determined accurately and conveniently with solution of β and G beam . Abstract: An improved plate model is proposed for the orthotropic double cantilever beam (DCB) specimens with an adhesive layer. The upper adherend of the DCB specimens was converted to a rectangular plate supported by a row of vertical springs and rotational springs at one end and subjected to a vertical uniform traction at the other end. The transverse deflection distributions of the present model along the width are determined using the Rayleigh-Ritz method. Then, combined with the virtual crack closure technique, the closed-form solutions for non-uniformity coefficient β and variation coefficient ν are obtained, from which the mode-I initiation fracture toughness can be determined precisely and conveniently.